Aesthetics, sense of place, and ecological education In the amazonian agricultural landscape - Vallejos Mundaca, Cesar Anderson (2025)
The recent urban expansion in the Tarapoto conurbation has significantly modified agricultural landscapes, thereby diminishing their capacity to provide cultural ecosystem services. This study analyzed the values of CES within the peri-urban agricultural landscape through the perspectives of farmers and local residents, employing 52 semi-structured interviews and participant observation. The findings revealed a direct connection between landscape configuration and cultural identity, demonstrating that economic viability, aesthetic appreciation, and sense of belonging are key components of the perceived CES in these agricultural settings. In terms of values, the economic aspect is associated with agricultural sustenance and income generation; the social aspect, with community cohesion and the transmission of traditional knowledge; and the symbolic aspect, with identity, history, and sense of place. This underscores the critical importance of understanding and safeguarding the complex interaction between socio-ecological systems and human well-being in agricultural contexts, with the aim of fostering urban sustainability.